Characteristic-Based Development Students Aspect - Wahyullah Alannasir (International Journal of Asian Education, 2020)
The characteristics of students from cognitive, affective, and psychomotor aspects so that educators are able to cultivate and develop the potential and talents of each student so that educators easily evaluate the strengths and weaknesses in learning. Different characteristics possessed by each student can provide an understanding for each educator to use strategies and methods in developing these different talents and potentials. Understanding the development of student characteristics can be seen from three aspects, namely cognitive, affective, and psychomotor aspects. The cognitive element is the domain that includes mental activities (brain). Emotional issues are those related to attitudes and values, which include behavioral traits such as feelings, interests, beliefs, emotions, and values. Psychomotor aspects are domains that include movement behavior and physical coordination, motor skills, and physical abilities of a person so that the skills that will develop if often practiced can be measured based on distance, speed, speed, technique, and manner of implementation. Analyzing students can be seen in four key factors that determine student success, including general characteristics (general characteristics), specific entry competencies (special initial abilities), learning styles (learning styles), and multiple intelligences (plural intelligences).